Mettere alla prova la sociologia pragmatica: le teorie cospirative come oggetto di ricerca - Caniglia, Enrico (SocietàMutamentoPolitica, 2021)
Pragmatic Sociology of Boltanski, Latour and others shows itself as a third way respect to two best known traditional French Sociologies: Pierre Bourdieu’s Critical Sociology and Raymond Boudon’s Sociology of Good Reasons. This essay points out the originality of the Pragmatic Sociology’s principles in the analysis of a controversial phenomenon: Conspirative Theory. It shows as Pragmatic Sociology manages to avoid the conspirationism typical of Bourdieu’s critical sociology, and the reductionism of Boudon’s sociology as well. However, Boltanski and Latour are not immune to the attitude to pathologize Conspirative Theory. Instead, a Pragmatic Sociology account should study the usage of the label “Conspirative Theory” as a rhetoric strategy of exclusion.